2006
DOI: 10.4067/s0034-98872006000300017
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfismo de la proteína ligante de ácidos grasos intestinal (FABP2), obesidad e insulina resistencia

Abstract: The genetic components of insulin-resistance, diabetes and obesity have been largely studied. These conditions are determined by multiple polygenic and environmental factors. Certain candidate genes, that have common functional variants in the general population, may be important determinants of inter-individual differences in the response to dietary changes. This review focuses in one of the major candidate genes, the gene encoding for the FABP2, an intracellular protein expressed only in the intestine, invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…In Latin America, the genotypic frequency of the Ala54Thr variant is equally variable according to the population studied, as it is in the rest of the world. For example, in Chilean aboriginal populations, an allele frequency of 18.2 % in Aymaras and 31.9 % in Mapuches has been found (16). Similarly, in Argentina, a recent study revealed an allelic frequency of 0.277 (95 % confidence limits 0.234-0.323) and genotypic frequencies of 40 % for heterozygous and 7.42 % for homozygous (17).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In Latin America, the genotypic frequency of the Ala54Thr variant is equally variable according to the population studied, as it is in the rest of the world. For example, in Chilean aboriginal populations, an allele frequency of 18.2 % in Aymaras and 31.9 % in Mapuches has been found (16). Similarly, in Argentina, a recent study revealed an allelic frequency of 0.277 (95 % confidence limits 0.234-0.323) and genotypic frequencies of 40 % for heterozygous and 7.42 % for homozygous (17).…”
Section: Discussionmentioning
confidence: 95%
“…The exposure proportion between cases was calculated at a 30 % level, OR detection limits of 4 and a case-control ratio of 1:3. The assigned value for was assumed by the literature review, which reflects similar data as used here (8). For calculation procedure, the program Epidat (4.2 version for Windows 64 bits) was used, obtaining a sample size of 144 individuals.…”
Section: Population Sample Size Calculation and Sampling Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…El polimorfismo de la "Fatty Acid Binding Protein 2" (FABP2) es uno de los genes candidatos que han sido asociados con RI y obesidad 36 . Esta proteína participa en el transporte de ácidos grasos de cadena larga a nivel intestinal.…”
Section: Factores Genéticosunclassified